2013
DOI: 10.5539/ass.v10n2p172
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Work Behavior (IWB) in the Knowledge Intensive Business Services (KIBS) Sector in Malaysia: The Effect of Leader-Member Exchange (LMX) and Social Capital (SC)

Abstract: Today, innovation is no longer belongs to the research and development (R&D) lab per se. In fact, innovation can be considered more of a product of the human creative mind with an inherent tacit knowledge. In order to be a successful knowledge-based economy, employees must continually be innovative. As such, this research which relates to innovation by and large will assist in creating better understanding of innovation from the behavioral perspective. In the context of business, innovation has long been embra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…LMX) and social capital (e.g. LMC) have been examined and supported by June and Kheng (2014) in the knowledge intensive business services sector in which employees' innovative work behavior is affected by LMX and social capital. This study complements previous research by specifying the theoretical linkage between LMX and LMC in depth from a teaming perspective.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…LMX) and social capital (e.g. LMC) have been examined and supported by June and Kheng (2014) in the knowledge intensive business services sector in which employees' innovative work behavior is affected by LMX and social capital. This study complements previous research by specifying the theoretical linkage between LMX and LMC in depth from a teaming perspective.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In other words, innovative behaviour can be seen as the production or adoption of new and useful ideas, processes, products or procedures within a work role, group or even an organization (De Jong & Den Hertod, 2007). It is important to note that this production or adoption of new and useful ideas is a multistage process of problem recognition (June & Kheng, 2014). As such, innovative employees are those who are consistently searching for and promoting new ideas with the aim of ultimately transforming those novel ideas into commercial product (Singh & Sarkar, 2012).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…From a theoretical view point, researchers should investigate technology and adoption processes on (family) farms beyond a focus on the owner-manager, incorporating workers into the unit of analysis. From a practical view point, support agents (e.g., extension) should pay more attention to workforce management and development (following Malanski et al ., 2017; Nettle, 2012; Nettle et al ., 2018) as well as to farmers’ transformative and inclusive leadership skills (see, e.g., June and Kheng, 2014), as these appear to be important factors in technology and practice adoption and more broadly in farms’ innovation capacity.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve this, managers must have the abilities to create an atmosphere in the organisation that stimulates workers’ involvement in innovations in technologies and practices (Anderson and West, 1998; Lukeš, 2013). Such abilities include: recognising workers’ good performance, motivating the sharing of knowledge and joint learning, promoting good relationships between workers, communicating the organisation's objectives clearly and proposing new ideas for developing the organisation (June and Kheng, 2014). Anderson and West (1998) have suggested that building an organisational atmosphere where innovation is incentivized entails: (i) promoting a group vision within the workforce, (ii) generating practices for stimulating good interpersonal relationships, (iii) continuously evaluating the innovation process, (iv) motivating workers to correct their mistakes and (v) involving workers in the generation and implementation of new ideas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation